Materialismo ecológico como materialismo de la reproducción: un diálogo entre Theodor Adorno y Raquel Gutiérrez Aguilar - Andrés F. Parra-Ayala (Revista de Estudios Sociales)
This article explores a dialogue between the philosophical frameworks of Theodor Adorno and Raquel Gutiérrez Aguilar. The central argument posits that Adorno’s ecological materialism—rooted in his critique of idealist philosophical systems and capitalism—converges with Gutiérrez Aguilar’s materialism of care and reproduction in their shared premise: there can be no human freedom without the freedom of nature. Adorno prefigures this perspective philosophically through his critique of the reification of the subject abstracted from nature and his concepts of natural history, differentiation without domination, and objective communication. Gutiérrez Aguilar, in turn, provides a grounded view, illustrating how certain political and communal practices among Indigenous and Black communities, as well as the life-sustaining work traditionally performed by women, reveal an emancipatory potential. This potential, though never devoid of complexity or tension, gestures toward a vision of differentiation without domination between humanity and nature.